Founder effects and stochastic dispersal at the continental scale of the fungal pathogen of bananas Mycosphaerella fijiensis - Rivas, G.G.; Zapater, M.F.; Abadie, C.; Carlier, J.
The worldwide destructive epidemic of the fungus Mycosphaerella fijiensis on banana started recently, spreading from South-East Asia. The founder effects detected in the global population structure of M. fijiensis reflected rare migration events among continents through movements of infected plant material. The main objective of this work was to infer gene flow and dispersal processes of M. fijiensis at the continental scale from population structure analysis in recently invaded regions. Samples of isolates were collected from banana plantations in 13 countries in Latin America and the Caribbean and in Africa. The isolates were analysed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP)and microsatellite molecular markers. The results indicate that a high level of genetic diversity was maintained at the plantation and the plant scales. The loci were at gametic equilibrium in most of the samples analysed, supporting the hypothesis of the existence of random-mating populations of M. fijiensis, even at the plant scale. A low level of gene diversity was observed in some populations from the Africa and Latin America-Caribbean regions. Nearly half the populations analysed showed a significant deviation from mutation-drift equilibrium with gene diversity excess. Finally, a high level of genetic differentiation was detected between populations from Africa (FST = 0.19)and from the Latin America-Caribbean region (FST = 0.30). These results show that founder effects accompanied the recent invasion of M. fijiensis in both regions, suggesting stochastic spread of the disease at the continental scale. This spread might be caused by either the limited dispersal of ascospores or by movements of infected plant material.
Keywords: BANANAS; FOUNDER EFFECTS; GENETIC POPULATION STRUCTURE; LONG-DISTANCE DISPERSAL OF FUNGI; MYCOSPHAERELLA FIJIENSIS